A Study on the stability of international reserve currency - Li, Kaida (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This article uses the dynamic analysis of the small country open economic framework (Obstfeld and Rogoff) to establish a basic supply and demand model of two countries, which solves the stable condition that the international reserve currency reaches the balance. The equilibrium stability condition of reserve currency is that the solvency growth rate of reserve currency countries is not lower than the real yield of reserve currency and the actual output growth rate of the non-reserve currency countries, while the reserve currency countries should have larger economic volume. The test of the Bretton Woods system and the contemporary international reserve currency system with stable conditions shows that the Bretton Woods system and the contemporary international reserve monetary system do not meet the stability conditions.